2018
DOI: 10.1002/2017gh000080
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Urban Housing Shape Dengue Distribution in Singapore at Neighborhood and Country Scales

Abstract: Dengue is the most important human arboviral disease in Singapore. We classified residential areas into low‐rise and high‐rise housing and investigated the influence of urban drainage on the distribution of dengue incidence and outdoor breeding at neighborhood and country scales. In Geylang area (August 2014 to August 2015), dengue incidence was higher in a subarea of low‐rise housing compared to high‐rise one, averaging 26.7 (standard error, SE = 4.83) versus 2.43 (SE = 0.67) per 1,000 people. Outdoor breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 45 publications
5
24
2
4
Order By: Relevance
“…Additionally, an increased frequency of movement within urban and predominantly residential neighbourhoods was found to increase the risk of dengue infection [ 66 ]. Patterns in urban area structure and population density could also influence the rate of dengue incidence, as agglomerations of high-rise buildings have a lower dengue incidence as compared to low-rise buildings [ 67 ]. Urban and rural areas with predominantly low-rise residential buildings with denser drainage networks could thus increase the breeding habitats of dengue vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, an increased frequency of movement within urban and predominantly residential neighbourhoods was found to increase the risk of dengue infection [ 66 ]. Patterns in urban area structure and population density could also influence the rate of dengue incidence, as agglomerations of high-rise buildings have a lower dengue incidence as compared to low-rise buildings [ 67 ]. Urban and rural areas with predominantly low-rise residential buildings with denser drainage networks could thus increase the breeding habitats of dengue vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Urban and rural areas with predominantly low-rise residential buildings with denser drainage networks could thus increase the breeding habitats of dengue vectors. [ 67 ]. While large differences in urbanisation demographics may potentially affect dengue preventive practices especially in Malaysia and Thailand with significant rural populations [ 68 ], multiple studies have shown that there is no large difference in dengue incidences between urban and rural areas in either Malaysia [ 69 , 70 ] or Thailand [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti in Singapore (Seidahmed, et al 2018), Brazil (Souza, et al 2017)m and Australia (Montgomery, et al 2004).…”
Section: Cross-correlation Analysismentioning
confidence: 99%
“…Most previous studies investigated the effects of either dynamic climate factors (Carvajal, Viacrusis, et al 2018, Zheng, et al 2019, Arcari, Tapper and Pfueller 2007, Tovar-Zamora, et al 2019, Bavia, et al 2020 or static spatial distributions of landscape attributes (Seidahmed, et al 2018, Vanwambeke, Lambin, et al 2007, Vanwambeke, N.Bennett and Kapan 2011, Sarfraz, et al 2012) on the temporal variations or spatial distributions of mosquito occurrence and dengue incidence. However, landscape and climate conditions can change concurrently in time and space, and their spatiotemporal interrelation may play a decisive role in determining the positive or negative effects on mosquitoes and dengue, such as interference during flood events.…”
Section: Introductionmentioning
confidence: 99%
“…Pessoas que vivem em casas térreas também foram consideradas sob risco, quando comparadas àquelas que moram em apartamentos 34,41 . Estudos prévios mostraram que a oviposição do mosquito é menor em construções mais altas, o que torna a participação dos prédios pequena nos índices de infestação 44,50 .…”
Section: Fatores Sociodemográficosunclassified